(untitled) (Research, Society and Development, 2021)
Analyzing the competitiveness scenario among companies, the purchasing sector has become a strategic sector, so it is possible to perceive the organizations’ constant search for strategic models that allow an alignment with the results expected by the corporations. The present article aims to propose an alternative method for strategic management in the acquisition of materials and services, through Peter Kraljic’s purchasing model, which analyzed the materials from the financial impacts caused by them and the risk of supplies that these represent. Alongside this is proposed the use of Game Theory as game strategy to be played for each group of material. For this, the method of research used was the hypothetical-deductive method, as well as the literature review, made through the reading of books, magazines and periodicals that report and relate to the subject. In the end, one of the observed results is a strategic matrix for acquisition of materials, where for each group of materials, after classified as financial risk and risk of supply a type of game is proposed. However, it is observed that the field of study is very vast and susceptible of new studies.